Alberuni Opinion about history of biology (Darwinism and Evolution A second document) (Eurasian Medical Research Periodical, 2023)
Abu-Alraihan Muhammad Ibn Ahamad Alberuni (362-440Ah , 973-1048 AD) an Arabic Moslem philosopher , astronomer , mathematician ,pharmacist and biology historian . His opinion about history of biology was expressed in one of the many books and treatises that he wrote which was translated to English language ; History of India . It was some 60-70 years ago when T.I.Rainow(1943) called attention to the fact that in this book India , his thoughts about natural selection , through struggle for life and survival of the fittest was expounded. Jan Z.Wilczynski (1959) published a paper about this presumed Darwinism of Alberuni as was expressed in his book India